FACTOR RELATED FATIGUE IN OIL AND GAS WORKER: LITERATURE REVIEW - Pramudita, Revi Adib; Lestari, Fatma (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Oil and gas workers are faced with environmental conditions that are at risk of experiencing work fatigue. The perceived work fatigue has an impact on reducing the level of work concentration, if this condition is left unchecked it will increase the risk of work accidents. This research aims to determine the factors associated with work fatigue in oil and gas workers. This research aims to determine the factors associated with work fatigue in oil and gas workers. Research methods used in literature review with the PRISMA approach (preferred reporting items for systematic reviews and meta-analyses). In the journal search carried out on a database google scholar and ScienceDirect with the keywords